Chemical digestion of palm oil mill effluent (pome) - Joshua, Bajau (Universiti Malaysia Sarawak, UNIMAS, 2013)
Palm oil industry in Malaysia shows a rapid growth as global demand is increasing. Consequently, the production of waste, especially palm oil mill effluent (POME) increases along with the palm oil production. The environment is in jeopardized as recent treatments method cannot meet the increasing volume of POME. Thus, chemical treatment is proposed as another alternatives method in order to develop an efficient and fast treatment for POME. In this study, chemical (oxidants) is used to remove biochemical oxygen demand (BOD) and chemical oxygen demand (COD) of POME. The best chemical is chosen between two common oxidants; hydrogen peroxide (H2O2) and sodium hypochlorite (NaOCl). The best chemical is chosen base on percentage of COD and BOD reduction and cost efficiency. Under proper condition, the percentage of COD reduction can be up to 95.28 % and BOD reduction up to 73.91%.